Blood TREM2 + AR + mononuclear cell as prostatic cancer screening or diagnosis marker and application of blood TREM2 + AR + mononuclear cell - WANG QIAOHUA; JIANG GUANMIN (2024)
The invention relates to the technical field of biomedicine, in particular to a blood TREM2 + AR + mononuclear cell as a prostatic cancer screening or diagnosis marker and application of the blood TREM2 + AR + mononuclear cell as the prostatic cancer screening or diagnosis marker. It is found for the first time that the proportion of mononuclear cells of a trigger receptor 2 and an androgen receptor which are co-expressed by myeloid cells in blood in a prostate cancer patient is obviously increased, and whether a subject suffers from the prostate cancer or not can be judged by detecting the level of the blood TREM2 + AR + mononuclear cells. The blood TREM2 + AR + mononuclear cell as a prostate cancer screening or diagnosis marker has non-invasive, non-invasive and efficient effects in detection, and has wide application prospects in preparation of a prostate cancer screening and diagnosis kit. 本发明涉及生物医学技术领域，特别涉及血液TREM2+AR+单核细胞作为前列腺癌筛查或诊断标志物及其应用。本发明首次发现血液中共表达髓系细胞表达的触发受体2和雄激素受体的单核细胞在前列腺癌患者中比例明显升高，通过检测所述血液TREM2+